DNA Vaccine Delivered by a Needle-Free Injection Device Improves Potency of Priming for Antibody and CD8+ T-Cell Responses after rAd5 Boost in a Randomized Clinical Trial - Graham, Barney S. (Public Library of Science, 2013)
BACKGROUND: DNA vaccine immunogenicity has been limited by inefficient delivery. Needle-free delivery of DNA using a CO(2)-powered Biojector® device was compared to delivery by needle and syringe and evaluated for safety and immunogenicity. METHODS: Forty adults, 18–50 years, were randomly assigned to intramuscular (IM) vaccinations with DNA vaccine, VRC-HIVDNA016-00-VP, (weeks 0, 4, 8) by Biojector® 2000™ or needle and syringe (N/S) and boosted IM at week 24 with VRC-HIVADV014-00-VP (rAd5) with N/S at 10(10) or 10(11) particle units (PU). Equal numbers per assigned schedule had low (≤500) or high (>500) reciprocal titers of preexisting Ad5 neutralizing antibody. RESULTS: 120 DNA and 39 rAd5 injections were given; 36 subjects completed follow-up research sample collections. IFN-γ ELISpot response rates were 17/19 (89%) for Biojector® and 13/17 (76%) for N/S delivery at Week 28 (4 weeks post rAd5 boost). The magnitude of ELISpot response was about 3-fold higher in Biojector® compared to N/S groups. Similar effects on response rates and magnitude were observed for CD8+, but not CD4+ T-cell responses by ICS. Env-specific antibody responses were about 10-fold higher in Biojector-primed subjects. CONCLUSIONS: DNA vaccination by Biojector® was well-tolerated and compared to needle injection, primed for greater IFN-γ ELISpot, CD8+ T-cell, and antibody responses after rAd5 boosting. TRIAL REGISTRATION: ClinicalTrials.gov NCT00109629